The biochemical properties of the ATPase activity of a 70-kDa heat shock protein (Hsp70) are governed by the C-terminal domains - Lopez-Buesa, Pascual (The National Academy of Sciences, 1998)
The cytosolic 70-kDa heat shock proteins (Hsp70s), Ssa and Ssb, of Saccharomyces cerevisiae are functionally distinct. Here we report that the ATPase activities of these two classes of Hsp70s exhibit different kinetic properties. The Ssa ATPase has properties similar to those of other Hsp70s studied, such as DnaK and Hsc70. Ssb, however, has an unusually low steady-state affinity for ATP but a higher maximal velocity. In addition, the ATPase activity of Hsp70s, like that of Ssa1, depends on the addition of K(+) whereas Ssb activity does not. Suprisingly, the isolated 44-kDa ATPase domain of Ssb has a K(m) and V(max) for ATP hydrolysis similar to those of Ssa, rather than those of full length Ssb. Analysis of Ssa/Ssb fusion proteins demonstrates that the Ssb peptide-binding domain fused to the Ssa ATPase domain generates an ATPase of relatively high activity and low steady-state affinity for ATP similar to that of native Ssb. Therefore, at least some of the biochemical differences between the ATPases of these two classes of Hsp70s are not intrinsic to the ATPase domain itself. The differential influence of the peptide-binding domain on the ATPase domain may, in part, explain the functional uniqueness of these two classes of Hsp70s.